ANALISIS PENGARUH BEBERAPA FAKTOR FUNDAMENTAL DAN RISIKO SISTEMATIK TERHADAP HARGA SAHAM Kasus Industri Barang Konsumsi Yang Go-Publik di Pasar Modal Indonesia - Syahib Natarsyah (Faculty of Economics and Business, Universitas Gadjah Mada, 2000)
This research is aimed at analyzing influence of several fundamental factors and systematic risk on stock price of consumption goods industries. The group of consumption goods industry has been chosen as research object considering that the products obstained are strategic consumption commodities badly needed by the society as a whole, in which they are not only in the form of nutricious food and drink, but also medicines, helth products, cosmetic, and other household basic necessities.The sample was taken by using non probability random sampling (purposive sampling method). The population cover 38 companies, while the taken sample consist of 16 companies, the research period of 8 years (1990 up to 1997). The data were analyzed by double log (log linear) model.The research result show that from the six factors assumed to influence on stock price of consumption goods industries under investigation, there are four factors which partially show positive and significant influence: return on assets (ROA), debt to equity ratio (DER), book value equity per share (BVES) with degree of less than 1% and systematic risk with degree of 10%. Actual influence of ROA on stock price is the same as the one happened in the previous research, which means that investors are very consistent inb applying performance finance from aspect of industry “earring power” in evaluating stock price. Book value equity per share as a dominant factor in influencing stock price, and this indicates that Indonesian investors tend to invest their capital in long run periods when value of equity pershare grows, wich reflects gurantee or claim on net assets provided by fims.Based on the research results, it is also discovered that fundamental factor and systematic risk have weak influence in explaining stock price variation at the Indonesian capital market, in which R2 is only 31%, which means that stock price variation is mostly determined by market psychology, that is non fundamental factors.